Analysis Of Compliance In Taking Anti-Tuberculosis Drug (Oat) On The Success Of Therapy In Drug-Sensitive Tuberculosis Patients At Muhammadiyah Ahmad Dahlan Hospital, Kediri City - Gading Nurantika; Chintia Devientasari; Hanik Maria Dewi; Hanie Kusuma Wardani (Strada Journal of Pharmacy, 2024)
Tuberculosis, also known as "tubercle bacilli" (TB), is a directly transmissible disease caused by the Mycobacterium tuberculosis bacteria. Tuberculosis is a leading infectious disease that causes death worldwide. The WHO also identified the importance of achieving a high level of patient compliance in TB treatment to control the spread of this disease. This study aims to measure the extent to which tuberculosis patients at Muhammadiyah Ahmad Dahlan Hospital in Kediri City adhere to their treatment, thus achieving the success of OAT (Anti-Tuberculosis Drugs) therapy. The results of this study are expected to provide insights into the relationship between medication adherence and treatment success in drug-sensitive TB patients, as well as offer recommendations for improving patient compliance in TB treatment. The design of this study is quantitative, utilizing a retrospective cohort research design. The study population consists of all pulmonary tuberculosis (TB) patients who have undergone TB treatment for six months at Muhammadiyah Ahmad Dahlan Hospital in Kediri City, totaling 42 individuals. The sample was taken using a total population sampling method. Data analysis was conducted using cross-tabulation analysis with a chi-square test. The results of the study revealed that 18 patients (43%) had high adherence, 19 patients (45%) had moderate adherence, and 5 patients (12%) had low adherence. The majority of patients, 41 individuals (98%), were cured, while 1 patient (2%) was not cured. The chi-square test results showed a p-value of 0.023<0.005. The conclusion of this study is that there is a correlation between adherence to anti-tuberculosis (OAT) medication and the success of therapy. It is recommended that the hospital pays closer attention and provides motivation for patients to continue their treatment until full recovery.